Ethnopharmaceutical Study of Plants as an Alternative Treatment Gastritis Baluwarti Society - Risma, Nindita Yoan; Saputri, Alip Desi Suyono; Anggraini, Truly Dian (Jurnal Biologi Tropis, 2024)
The Baluwarti community is a community that lives around the Surakarta Hadiningrat Palace with consist of princes relatives, courtiers, and ordinary people. Baluwarti community to currently still carrying out traditional medicine traditions by utilizing medicinal plants as a treatment in Baluwarti village, gastritis is included in the category of 15 diseases frequent highs. This research is an ethnopharmaceutical research aimed at to find out the local name of the plant, the part used, the way of processing, the rules usage, and treatment methods used as an alternative treatment of gastritis carried out by the community around the Surakarta Hadiningrat Palace. This research is descriptive research that uses quantitative methods. The analysis parameters used are: Use Value (UV), Informant Consensus Factor (ICF), Fidelity Level (FL), and Plant Part Value (PPV). Sampling technique using snowball sampling through open ended interview with the community around the Surakarta Hadiningrat Palace. Based on results interviews with 17 informants found 13 types of medicinal plants used as alternatives treatment of gastritis includes African plants, neem plants, cassava genderuwo, white turmeric, temulawak, cassava, and ginger are processed by boiling. In addition, breadfruit pace and white duwet that can be eaten immediately. Turmeric by processing is ground and grated, as well as aloe vera that is taken mucus using a spoon. The result of the ICF value obtained disease gastritis with a value of 0.25. Plant species that have the highest UV value with a value 0.647 and the highest FL yield of 64.70% is turmeric (Curcuma longa L.) while the PPV value obtained the use of plant parts that are most often used as medicinal materials traditional is 30% rhizome, 18% leaf, 12% fruit, 12% tuber, and 6% mucus.